Paternal heat exposure causes DNA methylation and gene expression changes of Stat3 in Wild guinea pig sons. Issue 9 (28th February 2016) - Weyrich, Alexandra; Benz, Stephanie; Karl, Stephan; Jeschek, Marie; Jewgenow, Katarina; Fickel, Joerns
Abstract: Epigenetic mechanisms convey environmental information through generations and can regulate gene expression. Epigenetic studies in wild mammals are rare, but enable understanding adaptation processes as they may occur in nature. In most wild mammal species, males are the dispersing sex and thus often have to cope with differing habitats and thermal changes more rapidly than the often philopatric females. As temperature is a major environmental selection factor, we investigated whether genetically heterogeneous Wild guinea pig ( Cavia aperea ) males adapt epigenetically to an increase in temperature, whether that response will be transmitted to the next generation(s), and whether it regulates mRNA expression. Five (F0) adult male guinea pigs were exposed to an increased ambient temperature for 2 months, corresponding to the duration of the species' spermatogenesis. To study the effect of heat, we focused on the main thermoregulatory organ, the liver. We analyzed CpG‐methylation changes of male offspring (F1) sired before and after the fathers' heat treatment (as has recently been described in Weyrich et al. [ Mol. Ecol ., 2015]). Transcription analysis was performed for the three genes with the highest number of differentially methylated changes detected: the thermoregulation gene Signal Transducer and Activator of Transcription 3 ( Stat3 ), the proteolytic peptidase gene Cathepsin Z ( Ctsz ), and Sirtuin 6 ( Sirt6 ) with function in epigenetic regulation. Stat3 gene expression was significantly reduced ( P  < 0.05), which indicated a close link between CpG‐methylation and expression levels for this gene. The two other genes did not show gene expression changes. Our results indicate the presence of a paternal transgenerational epigenetic effect. Quick adaptation to climatic changes may become increasingly relevant for the survival of wildlife species as global temperatures are rising. Abstract : As temperature is a major environmental selection factor, we investigated whether genetically heterogeneous Wild guinea pig ( Cavia aperea ) males adapt epigenetically to an increase in temperature, whether that response will be transmitted to the next generation(s), and whether it regulates mRNA expression. We detected heritable adaptation, and differential DNA methylation patterns accompanied with gene expression changes of the thermoregulation gene Stat3. Our findings indicate that this epigenetic response has on the one side ecological relevance and on the other an impact on evolutionary processes.